2015
DOI: 10.1038/nature14907
|View full text |Cite
|
Sign up to set email alerts
|

A new cyanogenic metabolite in Arabidopsis required for inducible pathogen defence

Abstract: SUMMARYThousands of putative biosynthetic genes in Arabidopsis thaliana have no known function, suggesting that there are numerous molecules contributing to plant fitness that have not yet been discovered1,2. Prime among these uncharacterized genes are cytochromes P450 upregulated in response to pathogens3,4. Starting with a single pathogen-induced P4505, CYP82C2, we used a combination of untargeted metabolomics and co-expression analysis to uncover the complete biosynthetic pathway to a previously unknown Ara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
231
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(240 citation statements)
references
References 28 publications
8
231
1
Order By: Relevance
“…While camalexin controls resistance to some B. cinerea isolates depending upon their genotype, little is known about how this phytoalexin may influence the interaction with a broad population of isolates (Kliebenstein et al, 2005;Bednarek et al, 2011;Rajniak et al, 2015;Frerigmann et al, 2016). Comparing the transcript accumulation for all the enzymes in the biochemical pathway and the final defense metabolite showed that while camalexin accumulation is highly diminished in the coi1-1 background, the transcriptional response of the genes encoding the biosynthetic enzyme is largely intact in this JA mutant ( Figure 4A; Supplemental Figure 1).…”
Section: Relative Importance Of Camalexin Mediated Defensementioning
confidence: 99%
“…While camalexin controls resistance to some B. cinerea isolates depending upon their genotype, little is known about how this phytoalexin may influence the interaction with a broad population of isolates (Kliebenstein et al, 2005;Bednarek et al, 2011;Rajniak et al, 2015;Frerigmann et al, 2016). Comparing the transcript accumulation for all the enzymes in the biochemical pathway and the final defense metabolite showed that while camalexin accumulation is highly diminished in the coi1-1 background, the transcriptional response of the genes encoding the biosynthetic enzyme is largely intact in this JA mutant ( Figure 4A; Supplemental Figure 1).…”
Section: Relative Importance Of Camalexin Mediated Defensementioning
confidence: 99%
“…As noted above, camalexin and 4OH-ICN are phytoalexins that function against bacterial, fungal, and oomycete pathogens (Rogers et al, 1996;Glazebrook et al, 1997;Ferrari et al, 2007;Schlaeppi et al, 2010;Wang et al, 2013;Rajniak et al, 2015) and also vary in our Arabidopsis lines. Whether these metabolites also function in deterring parasitic plants is an open question.…”
Section: Dodder Growth Is Enhanced On Glucosinolate-free Hostsmentioning
confidence: 99%
“…As noted above, the mutants exhibiting contrasting effects on dodder growth, atr1D and cyp79B2/B3, have opposite effects on levels of indole-3-acetaldoxime, a key precursor for multiple indole metabolites that function in development and defense. Known downstream species include auxin, camalexin, indole-3-carbonyl nitrile, and indole glucosinolates (Zhao et al, 2002;Glawischnig et al, 2004;Celenza et al, 2005;Rajniak et al, 2015), each of which merits consideration for potential involvement in host-plant resistance to dodder, as discussed below.…”
Section: Dodder Growth Is Enhanced On Glucosinolate-free Hostsmentioning
confidence: 99%
“…Regulatory mechanisms coordinating these processes are only beginning to be uncovered for some model metabolic pathways such as the metabolic pathways of the family of glucosinolates in Brassicacae (9). Coexpression analysis using information about gene and secondary metabolite cross-tissue expression patterns has been applied successfully to infer biosynthetic genes in secondary metabolism (4,10,11). In Arabidopsis, several "-omics"-based tissue atlases (e.g., for gene expression, alternative splicing, proteome) are publicly accessible to conduct such types of analysis (12).…”
Section: Significancementioning
confidence: 99%